Michael J. answered • 02/14/17

Tutor

5
(5)
Effective High School STEM Tutor & CUNY Math Peer Leader

g(x) = -4x

^{2}+ 4x - 5g(x - 1) = -4(x - 1)

^{2}+ 4(x - 1) - 5MaKayla F.

asked • 02/14/17Determine g(x-1) for the following function.

g(x)=-4^2+4x-5

Follow
•
3

Add comment

More

Report

Michael J. answered • 02/14/17

Tutor

5
(5)
Effective High School STEM Tutor & CUNY Math Peer Leader

g(x) = -4x^{2} + 4x - 5

g(x - 1) = -4(x - 1)^{2} + 4(x - 1) - 5

Mayuran K. answered • 02/14/17

Tutor

4.8
(24)
Patient and effective UH grad for High school Math tutoring

Hy Makayla,

Just follow the steps that Michael has shown you and your final answer would be as follows:

g(x-1) = -4(x - 1)^2 + 4 (x - 1) - 5

= -4 ( x^2 - 2x + 1) + 4x - 4 - 5

= -4x^2 + 8x - 4 + 4x - 9

= -4x^2 + 12x - 13

Good luck with the rest of your problems and hope you found my feedback helpful.

regards,

Mayuran

Ask a question for free

Get a free answer to a quick problem.

Most questions answered within 4 hours.

Find an Online Tutor Now

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.